Hamstring strain injury in athletes: A summary of clinical practice guideline recommendations (Journal of Orthopaedic & Sports Physical Therapy, 2022)
Hamstring strain injuries (HSIs) are common in sports that involve high-speed running, jumping, kicking, explosive lower extremity movements, or lifting objects from the ground. HSIs may result in considerable impairment, activity limitation, and participation restriction, including time lost from competitive sports. The high reinjury rate is also a challenge. Improving reinjury risk assessment and decision making for safe return to play is a high priority for all stakeholders.